INVESTIGATING ENGLISH EDUCATION MASTER STUDENTS' PERCEPTIONS ON EXTENSIVE READING STRATEGY - Kristian Florensio Wijaya (Polyglot, 2022)
Nowadays it is not sufficient enough for ELT educationalists to introduce their learners to L2 reading enterprises through one-way rigid trajectory; comprehension-based reading activities. Meanwhile, EFL learners critically demand more interactive, enjoyable, and comprehensive L2 reading learning enterprises. One of the exact representations of this coveted reading approach is manifested in the form of an extensive reading strategy. It is plausibly repudiated that extensive reading strategy can significantly foster EFL learners’ overall reading skills, vocabulary knowledge, and reading volition. This present small-scale qualitative study was enacted as one of the proactive attempts to profoundly investigate English Education Master Students’ perceptions on extensive reading strategy. To fulfill this main research objectivity, 15 English Education Master Students enrolling in Sanata Dharma University, Yogyakarta were invited to fill out the 10 items of the online Likert-scale questionnaire. 3 random interviewees were also selected from similar samplings to record their responses in correspondence with the 5 online open-ended written narrative inquiry questions. The research results unveiled that the majority of English Education Master Students have transformed into more competent L2 readers since they vigorously engaged in extensive reading activities and efficiently take better management over their extensive reading enterprises.   Bahasa Indonesia Abstrak: Dewasa ini tidak cukup bagi pengajar Bahasa Inggris untuk memperkenalkan peserta didik mereka ke usaha membaca bahasa kedua melalui lintasan kaku satu arah; kegiatan membaca berbasis pemahaman. Sementara itu, pelajar Bahasa Inggris secara kritis menuntut pembelajaran membaca bahasa kedua yang lebih interaktif, menyenangkan, dan komprehensif. Salah satu representasi tepat dari pendekatan membaca yang didambakan ini diwujudkan dalam bentuk strategi membaca ekstensif. Masuk akal untuk diakui bahwa strategi membaca ekstensif dapat secara luar biasa mendorong keterampilan membaca, pengetahuan kosakata, dan kemauan membaca pelajar Bahasa Inggris secara keseluruhan. Studi kualitatif skala kecil ini dilakukan sebagai salah satu upaya proaktif untuk menyelidiki secara mendalam mengenai persepsi Siswa Magister Pendidikan Bahasa Inggris tentang strategi membaca ekstensif. Untuk mewujudkan objektivitas penelitian utama ini, 15 Mahasiswa Magister Pendidikan Bahasa Inggris yang mendaftar di Universitas Sanata Dharma, Yogyakarta diundang untuk mengisi 10 item kuesioner skala likert online. 3 orang yang diwawancarai secara acak juga dipilih dari sampel yang sama untuk membagikan tanggapan mereka sesuai dengan 5 pertanyaan inkuiri naratif tertulis terbuka secara online. Hasil penelitian mengungkapkan bahwa sebagian besar Siswa Magister Pendidikan Bahasa Inggris telah berubah menjadi pembaca bahasa kedua yang lebih kompeten karena mereka giat terlibat dalam kegiatan membaca ekstensif dan secara efisien mengambil manajemen yang lebih baik atas usaha membaca ekstensif mereka.